2018
DOI: 10.1002/jbm.a.36423
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of PLGA formulation containing protein or peptide‐based antigen: Recent advances

Abstract: Protein or peptide-based antigens are the most promising forms to generate custom protective immune responses for clinical applications. Over the last decades, poly(lactic-co-glycolic acid) (PLGA) as a biodegradable polymer has gained more attention for delivery of protein and peptide. Besides many appropriate characteristics, to improve its properties to overcome some obstacles such as release profile and it is important instability of antigen during both encapsulation and storage. Therefore, optimized proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 156 publications
0
12
0
Order By: Relevance
“…However, some proteins are more sensible and need more sophisticated formulation systems for their stability. Usually, to increase the protein stability, stabilizers such as bovine serum albumin (BSA), succinylated gelatin or PEG are added to the water phase where protein solution is solubilized, to avoid protein degradation during the preparation process (Hajavi et al 2018 ; Panyam et al 2003 ; Van De Weert et al 2000 ). De Alteriis et al, successfully used BSA as protein stabilizer for vascular endothelial growth factor (VEGF) into PLGA MPs obtained by stamp-based method at room temperature exploiting solvent/non-solvent plasticization.…”
Section: Plga Mp Production Technique: Emulsification–evaporation Metmentioning
confidence: 99%
“…However, some proteins are more sensible and need more sophisticated formulation systems for their stability. Usually, to increase the protein stability, stabilizers such as bovine serum albumin (BSA), succinylated gelatin or PEG are added to the water phase where protein solution is solubilized, to avoid protein degradation during the preparation process (Hajavi et al 2018 ; Panyam et al 2003 ; Van De Weert et al 2000 ). De Alteriis et al, successfully used BSA as protein stabilizer for vascular endothelial growth factor (VEGF) into PLGA MPs obtained by stamp-based method at room temperature exploiting solvent/non-solvent plasticization.…”
Section: Plga Mp Production Technique: Emulsification–evaporation Metmentioning
confidence: 99%
“…Nevertheless, several reports have shown that optimized processing protocols allow that proteins encapsulated into polymer matrices or grafted to polymer scaffolds may preserve their native conformation and thus their bioactivity for several months (31)(32). The permeability of protein therapeutics through barriers such as the skin, mucosal membranes and cellular membranes is substantially reduced due to high molecular mass, which leads to injection being the primary mode of administration (33).…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…PLGA is approved by the FDA and European Medicines Agency in numerous drug transporter systems in humans (Prokop & Davidson, 2008). These NPs can act as delivery systems for trapping an antigen, mixing diverse antigens, or, more significantly, mixing adjuvants and antigens in the same particle (Hajavi, Ebrahimian, Sankian, Khakzad, & Hashemi, 2018). Furthermore, PLGA NPs, comprising very low doses of antigens and adjuvants, can stimulate robust T cell responses (Diwan, Elamanchili, Cao, & Samuel, 2004).…”
Section: Vector‐based or Particulate Delivery Systemmentioning
confidence: 99%